Expression of cytokine and apoptosis-related genes in bovine peripheral blood mononuclear cells stimulated with Brucella abortus recombinant proteins. (December 2016) - Im, Young; Jung, Myunghwan; Shin, Min-Kyoung; Kim, Suk; Yoo, Han
Abstract Brucellosis is a clinically and economically important disease. Therefore, eradication programs of the disease have been implemented in several countries. One hurdle in these programs is the detection of infected animals at the early stage. Although the protein antigens as diagnostic antigens have recently received attention, the exact mechanisms at the beginning of immune responses are not yet known. Therefore, genes encoding fiveB. abortus cellular proteins were cloned and the expressed recombinant proteins were purified. The expression of several cytokine genes (IL-1β, IL-4, IL-6, IL-12p40, IFN-γ, TNF-α, and iNOS) was analyzed in bovine peripheral blood mononuclear cells (bPBMC) after stimulation with the recombinant proteins. Three apoptosis-related genes, Bax, Bcl-2, and TLR4, were also included in the analysis to find out the adverse effects of the proteins to the cells. Each protein induced different patterns of cytokine expression depending on the stimulation time and antigen dose. Expression of IL-6, IL-12p40, and IFN-γ was induced with all of the proteins while IL-1β, IL-4, TNF-α, and iNOS gene expression was not. Expression of apoptosis-related genes was not altered except TLR4. These results suggest that the cellular antigens ofB. abortus induce both humoral and cellular immunity via the production of IL-6, IL-12p40, and IFN-γ in bPBMC without exerting any adverse effects on the cells.